THE CURRENT STATE OF DIAGNOSIS AND TREATMENT OF THE CONGENITAL TIBIA PSEUDOARTHROSIS - Khmyzov, Sergij; Katsalap, Yelizaveta (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Congenital pseudarthrosis of the tibia (CPT) is a rare disease that is detected with a frequency of 1 in 140–250,000 newborns. The disease is characterized by a wide range of clinical and radiological signs from progressive antecurvature deformation of the tibia to nonunion with a significant bone defect. Changes in the CPT area are caused by the influence of pathologically altered periosteum, which forms a fibrous hamartoma and is responsible for the deformity of the biomechanical properties of bone tissue. CPT can be formed at the moment of birth or developed spontaneously or as a result of minimal trauma in the early years. The main method of treatment of CPT is a surgery. Nowadays a number of surgical techniques, which are actively used and improved by specialists in the world, has been developed, The most used methods are the Ilizarovʼs method, application of intramedullary fixators, techniques with the use of vascularized tibial autograft, «induced membrane» technique. However, there are a few studies on comparing the effectiveness of different techniques or metal fixatives, most of them are presented in the format of a retrospective analysis of clinical cases series. This is due to the rarity of the disease and the lack of unified approaches on the choice of surgical treatment techniques. The main aim of surgical treatment of CPT is to achieve consolidation in the area of pseudoarthrosis, which may restore the limb resistance. The part of primary consolidation of CPT after using the surgical treatment various techniques varies very much, range from 60 to 100 %. The percentage of children with CPT tibial amputations has decreased significantly over the past 30 years, which generally indicates an improvement of the results of surgical treatment of the mentioned pathology. However, CPT still remains one of the most difficult diseases of pediatric orthopedics due to the large number of unsatisfactory results and complications after surgery.